La Duchesse d’Amalfi et la Querelle des femmes - Anny Crunelle Vanrigh (Sillages Critiques)
In The Duchess of Malfi, in which Linda Woodbridge and Christy Desmet have identified the influence of the Woman controversy, Webster replicates the epideictic model of early modern debates on the subject of woman between misogynists and philogynists. Issues of the Controversy – the nature of woman, gynocracy, marriage and celibacy, widowhood, access to the female body – are central to the play; the proclamations of the Duchess and the Aragonian brothers rehearse the cultural representations on both sides, while Webster’s monumentalizing of the Duchess reads like an attempt to add her name to the available catalogues of exempla. Yet the play’s structure with its system of parallels suggests its purpose is not so much to take sides in the debate as to hold a hermeneutic discourse on the production of polarised interpretive models.